Alternative Expressions of Citizen Voices: The Protest Song and Popular Engagements with the Mozambican State - Manhiça, Anésio; Shankland, Alex; Taela, Kátia; Gonçalves, Euclides; Maivasse, Catija; Tadros, Mariz (Institute of Development Studies, 2020)
This study examines Mozambican popular music to investigate three questions: Are notions of empowerment and accountability present in popular music in Mozambique? If so, what can these existing notions of empowerment and accountability reveal about relations between citizens and state institutions in general and about citizen-led social and political action in particular? In what ways is popular music used to support citizen mobilisation in Mozambique? The discussion is based on an analysis of 46 protest songs, interviews with musicians, music producers and event promoters as well as field interviews and observations among audiences at selected popular music concerts and public workshops in Maputo city. Secondary data were drawn from radio broadcasts, digital media, and social networks. The songs analysed were widely played in the past two decades (1998–2018), a period in which three different presidents led the country. Our focus is on the protest song, conceived as those musical products that are concerned with public affairs, particularly public policy and how it affects citizens’ social, political and economic life, and the relationship between citizens and the state.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; decentralization / descentralização; empowerment / empoderamento

O sector da educação em Moçambique: do acesso à qualidade epistémica do ensino primário - Mário, Mouzinho; Monjane, Celso M.; Santos, Ricardo (2020)
Desde os primeiros anos de independência nacional, em 1975, o objectivo central da política educativa de Moçambique tem sido o de assegurar que todas as crianças em idade escolar tenham acesso à escola e nela permaneçam até concluírem a educação básica. Na prossecução deste objectivo, a expansão do acesso ao ensino primário foi realizada com relativo sucesso, uma vez que já se alcançou uma taxa líquida de cobertura escolar de quase 100%. Contudo, o impressionante aumento das taxas de escolarização não tem sido acompanhado por uma correspondente melhoria da qualidade da aprendizagem, havendo, em relação a este aspecto, sinais preocupantes de um retrocesso considerável. Partindo desta observação, o estudo identifica e analisa as variáveis do contexto institucional por detrás da 'escolarização sem aprendizagem'. Os resultados do estudo apontam para a (i) fraca capacidade do Estado, (ii) excessiva dependência da ajuda externa e (iii) fraco envolvimento e participação das comunidades na gestão das escolas, como sendo os factores de maior influência na fraca qualidade da aprendizagem no ensino primário.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; citizenship & participation / cidadania e participação; education / educação; government policy / politica governamental; youth / juventude

The education sector in Mozambique: From access to epistemic quality in primary education - Mário, Mouzinho; Monjane, Celso M.; Santos, Ricardo (2020)
Abstract: From the early days of national independence in 1975, the central aim of the educational policy in Mozambique has been to ensure that all school-age children have access to school and can remain there until they have completed their basic education. In the pursuit of this aim, the extension of access to primary education was achieved relatively successfully, given that it reached a net rate of school coverage of almost 100 per cent. However, the impressive increase in school attendance rates has not been accompanied by a corresponding improvement in the quality of learning, and there are worrying signs of a considerable setback in relation to this aspect. Using this observation as a starting point, the study identifies and analyses the variables in the institutional context behind ‘schooling without learning’. The results of the study point to (i) weak state capacity; (ii) excessive dependence on external aid; and (iii) poor community involvement and participation in school management, as being factors with a major influence on the poor quality of education in primary schools.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; citizenship & participation / cidadania e participação; education / educação; government policy / politica governamental; youth / juventude